Effect of Alpha-lipoic Acid and Vitamin E in Diet on the Performance, Antioxidation and Immune Response in Broiler Chicken - Srilatha, T.; Reddy, V. Ravinder; Qudratullah, S.; Raju, M.V.L.N. (International Journal of Poultry Science, 2010)
An experiment was conducted to study the effects of alpha-lipoic acid at graded levels (0, 20, 40, 60, 80 mg/kg), Vit-E (10, 50 mg/kg) and their combination in a 5 x 2 factorial design on performance, anti-oxidation and immune response of broilers. 400 day-old male broilers were divided into 10 treatment groups, each with 8 replications (5 broilers in each) and fed one of the test diets till 6 weeks of age. Supplementation of Lipoic acid in broiler diet at 80 mg/kg gave significantly (p<0.05) higher BWG than control. The humoral immune response to NDV at 28 days age significantly (p<0.05) increased with lipoic acid at 20 and 80 mg/kg plus Vit-E 50 mg/kg. At 42 days age, HI titers were significantly (p<0.05) higher in all diets supplemented with lipoic acid than control. Cell mediated immunity was significantly (p<0.05) higher on diets that contained lipoic acid at 60 and 80 mg/kg than control. Similarly, Vit-E at 50 mg/kg also had significantly (p<0.05) higher CMI than Vit-E at 10 mg/kg. Supplementation of lipoic acid and vitamin E influenced the activities of lipid peroxidase. Inclusion of lipoic acid in all dietary treatment groups increased glutathione peroxidase levels. RBC catalase levels significantly (p<0.05) increased on diets that contained lipoic acid at 60 mg/kg. It is concluded that alpha - lipoic acid at 80 mg/kg and Vitamin E at 50 mg/kg may be supplemented to the broiler diet for improved growth, antioxidant status and better immune responses.